Effect of lactation management training on feeding pattern from birth to 6 months of age - Rulina Suradi; Sujana Jatiputra; Anthony Tan; Gulardi H. Wiknjosastro; Lukman Tarigan (Paediatrica Indonesiana, 1999)
This quasi-experimental study involved 13 health centers (Puskemas) in Jakarta. Six hundred and four pregnant women were recruited.Â  They were divided in to two groups. Subjects in Group 1 were given 3 Limes extra-training In breastfeeding management, i.e. at recruitment then during hospitalization for delivery and lastly at one month follow-up. Subjects in Group 2 was only given #roullnc #informaton at the health ccnu'cs where Lhcy did their antenatal care. Duta were collected at recruitment (in the last uimcstcr of pregnancy), 0.1 birth, and every month thereafter for six months. At recruitment there were no sib1J1ificanl diITcrcncc the two groups regarding age of the mOlher, parity, number of living chddren, and age of the last livrng chlld. At bIrth 96.2% of Group 1 mothers started breaslfeeding soon after birth and only 80.5% of Group 2 mothers did so. Prelacleru feedmgs were given to 20.5% of babies of Group 2 and only 5.5% of babies of Group 1; the difTerence statistically significant. The kind of prelacteal feed also dIffered between the two groups. Water was the most frequentÂ  preioctcai feed given by Group I mothers while in Group 2 mothers it was milk formula. At the nge of 6 months there was no difference between the two groups in the proportion of breastfeeding (99.2% in Group 1 versus 98,7% in Group 2 mothers). The proportion of exclusive breast feeding at the age of 4 months was 60.7% in Group 1 and 36.70/0 in Group 2. We conclude ulal extra training to pregnant and ncw mothers may change their attitude and skill in feeding their infants.